1988
DOI: 10.1007/bf03259941
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Sexual Dysfunction

Abstract: A large body of data, as well as clinical experience, link prescribed medications and substances of abuse with sexual dysfunction. This review surveys the relevant literature and summarises key points relating various classes of medications and their possible sexual side effects. Surprisingly, there were very few carefully designed, well organised, systematic studies of the effects of medication upon sexual performance. The preponderance of data is in the form of either case studies or collections of patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…In this article, we update information given in an earlier review of drug-induced sexual dysfunction (McWaine & Procci 1988). Recent advances made in sexual physiology are highlighted and an outline describing our diagnostic and treatment approach is presented.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this article, we update information given in an earlier review of drug-induced sexual dysfunction (McWaine & Procci 1988). Recent advances made in sexual physiology are highlighted and an outline describing our diagnostic and treatment approach is presented.…”
Section: Discussionmentioning
confidence: 97%
“…Recent work has shown that variable inhibition of the reuptake of noradrenaline and serotonin can be seen with the different heterocyclic agents based on their chemical configuration (McWaine & Procci 1988;Wein & van Arsdalen 1988). Recent work has shown that variable inhibition of the reuptake of noradrenaline and serotonin can be seen with the different heterocyclic agents based on their chemical configuration (McWaine & Procci 1988;Wein & van Arsdalen 1988).…”
Section: Antidepressantsmentioning
confidence: 99%
“…Examples of drugs implicated as a cause of ED include hydrochlorothiazides and beta-blocking agents. Medications used to treat depression, particularly the SSRIs such as citalopram (Celexa), escitalopram (Lexapro), fluoxetine (Prozac, Prozac Weekly, Sarafem), fluvoxamine (Luvox, Luvox CR), paroxetine (Paxil, Paxil CR, Pexeva) and sertraline (Zoloft), may also contribute to ED 9. Bupropion (Wellbutrin) which has a predominant effect on blocking the reuptake of dopamine is an antidepressant with lower incidence of ED 10.…”
Section: Overview Of Physiological Changes and Other Risk Factorsmentioning
confidence: 99%
“…8,9 SD has also been attributed to other physical, clinical factors and psychological factors. 5,[10][11][12][13][14][15][16][17][18][19] Research on erectile dysfunction patients indicate that SD has significant adverse effects on both physical and mental health dimensions of quality of life (QOL). [20][21][22][23][24] Sexual dysfunction data for Asian populations are scant and primarily clinic-based.…”
Section: Introductionmentioning
confidence: 99%